Impatience, Anticipatory Feelings and Uncertainty: A Dynamic Experiment on Time Preferences - Marco Casari; Davide Dragone (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
We study intertemporal choices through an experiment that elicits a subject's plan and then tracks its implementation over time. There are two main results. When facing a costly task to be completed under a deadline, two thirds of subjects prefer anticipating it rather than postponing it. Choice reversals are common although present-biased preferences alone cannot explain them. This evidence is compatible with models based on anticipatory feelings and stochastic utility.
Keywords: C91; D01; D80; D90; 330